Grundtvig, dyden og kærligheden - Nyborg, Ole (Grundtvig-Studier, 2010)
Grundtvig, dyden og kærligheden [Grundtvig, virtue and love] By Ole Nyborg In the writings and sermons of N. F. S. Grundtvig the concept of “virtue” is an important theme. However, its importance has been largely ignored in research on the theology of Grundtvig. Grundtvig’s scheme of virtue has important similarities with the biblical and also with the classical theory of virtue which we find in the works of Plato and Aristotle. The concept of virtue currently plays a prominent part in Neo-Aristotelian ethics and philosophy and the basic thinking of Grundtvig might be compared with this modem revitalization of classical virtue theory. In the sermons of Grundtvig in Vartov Church in the period 1839-1849, Christian love, righteousness, and goodness are understood through a general concept or scheme of virtue. The good fruits come from the good tree. No fruits of value can possibly come from a bad tree. The object of Christian learning and growth is to attain excellence or mastery of virtue. Acts of love are not a product of will-power or merely a result of individual decisionmaking. Acts of love come naturally from a certain inner virtuous character. Christ is the master of the Christian congregation which is a sort of “praxis” or community of learning. The quality of virtue is learned and acquired gradually in an intimate relationship and direct interaction with the living, active, and present master. A newcomer to this Christian congregation is like a small, powerless and incompetent child but in a process of learning and growth this child acquires virtue, knowledge, ability, motivation and competence in the community with the master or father of the true Christians. Because of the constant aggressiveness of the evil world outside, this learning and development can only be realized in a protected context behind the walls of this community, the “Wall of Paradise”.